Inovasi dan Pembaharuan Manajemen Pendidikan Islam: Abidatil Qinni, Sri Minarti - Qinni, Abidatil; Minarti, Sri (MATAAZIR: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study aims to determine the concept of innovation and renewal in Islamic education management. This research uses a type of library research with a qualitative approach and descriptive analysis. This research data collection technique is in the form of notes, previous research journals, articles and so on. While data analysis is carried out using three stages, namely data reduction, data display and drawing conclusions. The results showed that innovation and renewal of Islamic education management have the same meaning to improve the efficiency, quality, and relevance of education while maintaining the basic values of Islamic teachings, and the role of innovation in renewing Islamic education management includes several things including the quality of education, adjusting to the times, strengthening the implementation of Islamic values and so on.